UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI MINYAK DAN GAS BUMI (GAS ALAM) MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI KELAS XI MIPA-3 SMA NEGERI 1 KEMBANG TANJONG - Armani Armani (Universitas Jabal Ghafur, 2022)
The purpose of this study was to determine student learning outcomes on the material Oil and Gas (Natural Gas) taught through the Problem Based Learning (PBL) learning model in class XI MIPA-3 SMA Negeri 1 Kembang Tanjong. This study uses a descriptive qualitative approach with the type of Classroom Action Research (CAR). The data sources are students of class XI MIPA-3 SMA Negeri 1 Kembang Tanjong for the academic year 2021/2022, totaling 25 students. The criteria for each action consist of process criteria and outcome criteria. The process criteria are achieved if the student's action observation score is 80% and the result criteria is achieved if 85% of students get a score of 80 on the final action test. From the processing results, classical student learning outcomes have increased respectively by 44% and 12% with the percentage of completeness from 32% in the pre-cycle, 76% in the first cycle, and to 88% in the second cycle. The activity of teachers and students in learning by applying the Problem Based Learning (PBL) model has increased. Teacher activity increased by 16% from 77.33% to 93.33%, while student activity increased by 13.34% from 73.33% to 86.67%. Based on the results of the analysis, it can be concluded that the application of Problem Based Learning (PBL) can improve student learning outcomes on oil and natural gas (Natural Gas) materials in Class XI MIPA-3 SMA Negeri 1 Kembang Tanjong, and can also increase the activity of teachers and students in learning. by applying the Problem Based Learning (PBL) learning model.Keywords: Learning outcomes, Problem Based Learning (PBL) learning model.